EFFECTIVENESS OF CHEWING MARSHMALLOW CONTAINING BETEL CHEW ON SALIVARY Streptococcus mutans IN 12 YEARS OLD CHILDREN OF SMPN 29 PALEMBANG - Meidi Tri Yudha; Misnaniarti Misnaniarti (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
Marshmallow is a favored type of soft candy among children and adults. Betel chew added to marshmallow was reported containing antibacterial substances. The aim of this study was to determine the effect of chewing marshmallow containing betel chew on salivary S. mutans in 12 years old children. This experimental research was done with pretest and posttest control group design involving 30 subjects with DMFT range 3-5. Subjects were divided into group 1 (marshmallow containing betel chew) and group 2 (plain marshmallow). Saliva was collected before and after chewed marshmallow containing betel chew and plain marshmallow. Streptococcus mutans colonies were evaluated with colony counter. Data were analysed using pair T-test & independent T-tests. Paired-t test showed that the number of S. mutans colonies was significantly reduced after chewed marshmallow containing betel chew p=0,00 (p